Increased expression of urotensin II is associated with poor prognosis in hepatocellular carcinoma - Liu, Dian-Gang (Oncol Lett, 2016)
Urotensin II (UII) and the urotensin II receptor (UT) exhibit mitogenic effects on tumor growth. Our previous study demonstrated that the UII/UT system is upregulated in hepatocellular carcinoma (HCC) and may enhance the proliferation of human hepatoma cells. However, the clinical significance of UII/UT expression in HCC remains unclear. The present study assessed UII messenger RNA (mRNA) expression in 129 surgical specimens obtained from HCC patients using reverse transcription quantitative-polymerase chain reaction. The association between UII mRNA expression and clinicopathological parameters and overall survival rates was also investigated. The results revealed that UII and UT mRNA expression was significantly increased in HCC tissue compared with adjacent non-cancerous liver tissue (P<0.001). Furthermore, a significant correlation was identified between UII expression and histological differentiation (P<0.01), tumor size (P<0.01) and tumor stage (P=0.026). Kaplan-Meier survival analysis indicated that overall survival time was significantly shorter in patients with high UII expression, compared with those with low UII expression (P<0.001). Multivariate analyses indicated that UII expression was an independent predictor of overall survival (odds ratio, 1.12; P<0.001). In addition, UII mRNA was correlated with vascular endothelial growth factor mRNA expression. Therefore, UII expression is an independent biomarker for the prognosis of patients with HCC and thus, the UII/UT system may present a novel therapeutic target for the treatment of HCC.